Declaring war : congress, the president, and what the constitution does not say - Hallett, Brien (Cambridge : Cambridge University Press, 2012)
'Declaring War directly challenges the 200-year-old belief that the Congress can and should declare war. By offering a detailed analysis of the declarations of 1812, 1898 and the War Powers Resolution of 1973, the book demonstrates the extent of the organizational and moral incapacity of the Congress to declare war. This book invokes Carl von Clausewitz's dictum that'war is policy' to explain why declarations of war are an integral part of war and proposes two possible remedies - a constitutional amendment or, alternatively, a significant reorganization of Congress. It offers a comprehensive historical, legal, constitutional, moral and philosophical analysis of why Congress has failed to check an imperial presidency. The book draws on Roman history and international law to clarify the form, function and language of declarations of war, and John Austin's speech act theory to investigate why and how a'public announcement' is essential for the social construction of both war and the rule of law'--
Includes bibliographical references (pages 257-263) and index.
Keywords: War, Declaration of -- United States; War and emergency powers -- United States